MethSemble-6mA: an ensemble-based 6mA prediction server and its application on promoter region of LBD gene family in Poaceae - Sinha, Dipro; Dasmandal, Tanwy; Paul, Krishnayan; Yeasin, Md; Bhattacharjee, Sougata; Murmu, Sneha; Mishra, Dwijesh Chandra; Pal, Soumen; Rai, Anil; Archak, Sunil (Frontiers in Plant Science, 2023)
The Lateral Organ Boundaries Domain (LBD) containing genes are a set of plant-specific transcription factors and are crucial for controlling both organ development and defence mechanisms including anthocyanin synthesis, nitrogen metabolism, etc. It is imperative to understand how methylation regulates their expression, particularly through predicting methylation sites of their promoters in major crop species. In this study, we have developed a user-friendly prediction server for accurate prediction of 6mA sites by incorporating a robust feature set viz Binary Encoding of Mono-nucleotide DNA (MBED). Our developed model namely MethSemble-6mA outperforms other state-of-art tools in terms of accuracy (93.12%).Furthermore, we essay the pattern of probable 6mA sites at the upstream promoter regions of the LBD domain-containing genes in Triticum aestivum, and its allied species using the developed tool. On average each selected species had four 6mA sites and it was found that with speciation and due course of evolution in wheat, frequency of methylation has reduced significantly and few sites remain conserved. This obviously cues gene birth and gene expression alteration through methylation over time in a species and reflects functional conserveness throughout evolution. Since DNA methylation is a vital event in almost all plant developmental processes (e.g., genomic imprinting and gametogenesis) along with other life processes, our findings on epigenetic regulation of LBD domain-containing genes have dynamic implications in basic and applied research. Additionally, our developed server, MethSemble-6mA (http://cabgrid.res.in:5799/)will serve as a first-rate resource for a plant breeder willing to pursue epigenetic-based crop improvement research.